The Hellenic Institute established 1993 - Dendrinos, Charalambos; Vassiadis, George Andrew (The Hellenic Institute, Department of History, Royal Holloway, University of London, 2017)
Die Seite informiert über die Aktivitäten, das Forscherteam und die Projekten des The Hellenic Institut der Royal Holloway University of London.